THE EFFECT OF MORINGA LEAF EXTRACT (MORINGA OLEIFERA L) AGAINST MOTILITY OF SPERMATOZOA MICE EXPOSED TO MONOSODIUM GLUTAMATE - Ilham Saptia Nugraha; Wibisono, Dimas Sindhu; Saraswati, Indah; Juniarto, Achmad Zulfa (Indonesian Journal of Urology, 2022)
Objective: Excessive use of MSG in everyday life can cause infertility to men. Exposure to MSG can cause cells to experience oxidative stress which subsequently triggers the generation of free radicals. Free radicals can be resisted with antioxidants. Material & Methods: This research was a laboratory experimental test with a post-test only control group design using male mice as the experimental object. The statistical test used the One Way ANOVA test. Results: In this research, 5 male mice were assigned into 4 groups and 1 control group. Using the One Way ANOVA test, it was found that there were significant differences in ≥ 2 treatment groups in the motility group of spermatozoa with active movement (p < 0.001) and the motility group of spermatozoa with weak movement (p = 0.036). The two groups showed significant differences. The Post hoc LSD test in the motility group with active movement showed significant differences between the control group with MSG treatment (p < 0.001) and the treatment group given Moringa leaves extract of 600 mg/kgW (p < 0.001) and 1200 mg/kgW (p < 0.001). Conclusion: Moringa leaves extract can effect the improvement of the motility of spermatozoa exposed to monosodium glutamate at a given dose of 300 mg/kgW and 600 mg/kgW.